Tidally induced cross-shore sand-mud transport and long term bed profile evolution - Mohammad Fadhli Ahmad (University of Dundee, 2012)
A numerical study on the transport of sediments involving sand and mud mixture and associated long-term morphological changes under cross-shore tidal current is presented.